Evaluation of the surface roughness of three heat-cured acrylic denture base resins with different conventional lathe polishing techniques: A comparative study - Duggineni Chalapathi Rao; N Kalavathy; H S Mohammad; A Hariprasad; C Ravi Kumar (Wolters Kluwer Medknow Publications, 2015)
Purpose: Surface roughness promotes adhesion and colonization of denture plaque. Therefore, it is important to know the effects of polishing and finishing on the surface roughness of various acrylic resin materials. Objectives: To evaluate and compare the effects of different conventional lathe polishing techniques on heat cured acrylic resins in producing surface roughness. Materials and Methods: Three different commercially available heat-cured acrylic resin materials namely DPI, Meliodent and Trevalon Hi were selected. 30 Specimens of each acrylic material (30 x 3 = 90, 10 x 60 x 2mm) were prepared and divided into 5 groups, each group consisted of 6 Nos. of specimens per material(6x3=18) and were grouped as Group A(unfinished), Group B (finished), Group C (Polishing Paste), Group D (Polishing Cake) and Group E (Pumice and Gold rouge). The resulted surface roughness (µm) was measured using Perthometer and observed under Scanning Electron Microscope. The values obtained were subjected statistical analyses. Results: Among the materials tested, better results were obtained with Trevalon Hi followed by Meliodent and DPI. Among the polishing methods used, superior results were obtained with universal polishing paste followed by polishing cake; Pumice and Gold rouge. Although Pumice and Gold rouge values produced greater roughness value, they were well within the threshold value of 0.2 mm.